Incidental Brain MRI Findings in Children: A Systematic Review and Meta-Analysis - Dangouloff-Ros, V.; Roux, C.-J.; Boulouis, G.; Levy, R.; Nicolas, N.; Lozach, C.; Grevent, D.; Brunelle, F.; Boddaert, N.; Naggara, O. (American Journal of Neuroradiology, 2019)
BACKGROUND: The detection of incidental findings on children’s brain MR imaging poses various practical issues because the life-long implications of such findings may be profound.PURPOSE: Our aim was to assess the prevalence and characteristics of incidental brain MR imaging findings in children.DATA SOURCES: Electronic databases (PubMed, EMBASE, and Cochrane) were searched for articles published between 1985 to July 2018, with the following search terms: “incidental,” “findings,” “brain,” “MR imaging.”STUDY SELECTION: Inclusion criteria were the following: 1) patients younger than 21 years of age, 2) healthy children without any clinical condition, 3) MR images obtained with at least a 1.5T magnet, 4) original articles, and 5) a methodologic quality score of >=10.DATA ANALYSIS: Two observers independently extracted data and assessed data quality and validity. The number and type of incidental findings were pooled. Heterogeneity was assessed using the Cochran Q statistic and the I2 statistic.DATA SYNTHESIS: Seven studies were included, reporting 5938 children (mean age, 11.3 extpm 2.8 years). Incidental findings were present in 16.4% (99% CI, 9.8–26.2; Q = 117.5, I2= 94.9%) of healthy children, intracranial cysts being the most frequent (10.2%, 99% CI, 3.1–28.5; Q = 306.4, I2 = 98.0%). Nonspecific white matter hyperintensities were reported in 1.9% (99% CI, 0.2–16.8; Q = 73.6, I2 = 94.6%), Chiari 1 malformation was found in 0.8% (99% CI, 0.5–1.3; Q = 7.6, I2 = 60.5%), and intracranial neoplasms were reported in 0.2% (99% CI, 0.1–0.6; Q = 3.4, I2 = 12.3%). In total, the prevalence of incidental findings needing follow-up was 2.6% (99% CI, 0.5–11.7; Q = 131.2, I2 = 95.4%). Incidental findings needing specific treatment were brain tumors (0.2%) and cavernomas (0.2%).LIMITATIONS: Limitations were no age stratification or ethnicity data and variation in the design of included studies.CONCLUSIONS: The prevalence of incidental findings is much more frequent in children than previously reported in adults, but clinically meaningfull incidental findings were present in <1 in 38 children.IFincidental finding